The Role of “Scale” on the Acceleration of Social Interaction in Urban Spaces - Kaveh Hajialiakbari; Mohammad Zare; Mitra Karimi (Alanya Hamdullah Emin Paşa Üniversitesi, 2022)
Rehabilitation projects are interventions that can lead to the transformation of the socio-spatial structure of obsolescent neighborhoods. The main intention of such projects is the creation and/or improvement of social interactions after physical and functional interventions. Urban Renewal Organization of Tehran (UROT) is tasked with identification of target obsolescent neighborhoods, preparation of neighborhood development plans and implementation of rehabilitation projects to improve the quality of space and stimulate social interactions. In this paper, three urban spaces in different scales (“micro” for neighborhoods, “meso” for local and “macro” for trans-local scales), designed and implemented by UROT, were selected as a case study. By designing and filling a questionnaire and after analyzing research findings, the effect of the scale of the urban project on different activities was evaluated based on the Gehl model. Overall, in the expanded model based on the scale of space, an inverse ratio between the scale of space and both optional selective and social activities has been revealed.